The Impact of Bio-Based Fertilizer Integration Into Conventional Grassland Fertilization Programmes on Soil Bacterial, Fungal, and Nematode Communities - Ryan, Demi; Karpinska, Anna; Forrestal, Patrick J.; Ashekuzzaman, S. M.; Kakouli-Duarte, Thomais; Dowling, David N.; Germaine, Kieran J. (Frontiers in Sustainable Food Systems, 2022)
Phosphorus (P) is an essential plant macro-nutrient applied to soil in agriculture, mainly sourced from non-renewable mined phosphate rock, of which readily accessible reserves are currently under pressure, while global food demand continues to grow. Meanwhile, an abundance of P is lost in waste streams. Hence, bio-based fertilizers are increasingly produced using nutrient-recovery technologies and evaluated as a sustainable inorganic fertilizer alternative. However, there is little knowledge of how these products affect soil microorganisms. Soil bacterial, fungal and nematode community responses were studied in a field trial on four phosphate bio-based fertilizers (two struvite and two incinerator ashes), integrated into a conventional grassland fertilization program. Community data were obtained by amplicon sequencing of DNA extracted from soil samples and subsequent analysis of community composition, diversity and influencing environmental variables. Diversity of the soil microorganisms was maintained by all bio-based fertiliser treatments. The communities of struvite treated soil were similar to those in conventional mineral and organomineral P control treatments. However, communities in ash treatments were more disturbed, possibly due to high pH and heavy metal content. The order of dominating bacterial phyla changed with ash application, while there was a significant shift in the phylogenetic composition of fungal communities. The abundance of nematodes belonging to the order Dorylaimida, which are sensitive to environmental disturbance, were significantly reduced by ash derived from sewage sludge but not by the poultry litter ash. Significant changes in bacterial and fungal taxa abundances were found under the cattle slurry organomineral treatment, which appeared to be mainly due to the stimulation of copiotrophic organisms with organic input. Additionally, the abundance of bacterial feeding nematodes belonging to the order Rhabditida were increased in this treatment when compared to those in the unfertilized and mineral P control treatments. While nematode diversity was lowest in the unfertilized control, the presence of omnivorous dorylaimids in high numbers, reflected a least disturbed and mature soil environment. Overall, results indicated that in terms of soil bacterial, fungal and nematode communities, struvite can be utilized as an alternative source of P in conventional grassland fertilization programs, while the ash products require further investigation.